Белоснежка и семь гномов: сказки / Гримм, братья - Гримм Вильгельм Карл (Читаем детям, 2011)
Экземпляры: СФ (201308) / Инвентарный номер: 48472 / Цена: 54.00 / Сис.шифр: Д / Авт.знак: Г 84 / ГРНТИ: 17.82 / ББК: 84(4Гем)